1979
DOI: 10.1007/bf00418582
|View full text |Cite
|
Sign up to set email alerts
|

Rate of drying and the survival of microorganisms

Abstract: The survival rate of cells of the genera Arthrobacter, Pseudomonas, Mycobacterium, Escherichia, Micrococcus and Saccharomyces when counted immediately after fast or slow drying (20 minutes and 24 hours, respectively) was rather similar. However, after prolonged periods of dry storage, the number of viable cells after slow drying was much higher as compared with the rapidly dried cells. Investigations with Escherichia coli demonstrated this phenomenon only when more than about 8 mg of water per 10(8) cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Such a phenomenon could be prevented by a remoistening step, as demonstrated by the similar behavior of cells which were rapidly dried, remoistened, and slowly redried and cells which were only slowly dried. These results are in good agreement with the previous report of Antheunisse and Arkesteijn-Dijksman (2), who suggest that the cells are torn by rapid drying.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Such a phenomenon could be prevented by a remoistening step, as demonstrated by the similar behavior of cells which were rapidly dried, remoistened, and slowly redried and cells which were only slowly dried. These results are in good agreement with the previous report of Antheunisse and Arkesteijn-Dijksman (2), who suggest that the cells are torn by rapid drying.…”
Section: Discussionsupporting
confidence: 93%
“…Cells that were dried in less than 3.4 h subsequently died during a 5-day storage period. Moreover, the lowest water content per specimen to which R. meliloti RCR2011 could be rapidly desiccated without causing serious damage was determined by comparison with the work of Antheunisse and Arkesteijn-Dijksman (2). These authors reported that harmful effects of rapid drying on survival during storage at 31% RH occurreci VOL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is probably that the dehydration rate was much faster in the thin layers of manure. It has been shown that a fast dehydration process results in increased microbial inactivation [12]. On the other hand, long term survival is improved by a low a w and maximum survival of dried cells is expected when the dehydration rate is slow and the ultimate water activity low.…”
Section: Discussionmentioning
confidence: 99%
“…In a state of dry anabiosis, metabolic processes within the living spore are slowed or halted, which extends shelf-life during storage at reduced moisture. A variety of factors (stresses) have been reported to infl uence viability loss of micro-organisms in the drying process including: temperature (Bigelow and Esty, 1920); drying rate (Antheunisse and Arkestelin-Dilksman, 1979); and fi nal cell moisture content (Josić, 1982). While kinetic and probabilistic models have been used for over 40 years in the food industry to predict microbial death during thermal and drying operations (McMeekin and Ross, 2002), those conditions are often severe whereas death rate predictions for drying microbial cells involves more mild processing environments.…”
Section: Introductionmentioning
confidence: 99%